2013
DOI: 10.2355/isijinternational.53.2080
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Particle Descending Velocity in the COREX Shaft Furnace with DEM Simulation

Abstract: Screws in COREX shaft furnace are used to discharge burdens to the latter processor -the melter gasifier. They play a very important role in the uniform drawdown pattern, which directly affects the uniform gas distribution and further the smooth operation in the COREX shaft furnace. Therefore, a three dimensional model is established based on the discrete element method (DEM) in the present work. The model is used to investigate the effect of the bottom diameter of COREX shaft furnace, the cylinder height and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
36
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 27 publications
(28 reference statements)
2
36
0
Order By: Relevance
“…So far, DEM has become one of the most powerful simulation methods for granular behaviors. In the ironmaking field, many researches [5][6][7][8] had been studied about the granular behavior based on DEM, and the simulation results coincided well with the experiments and industrial operation. It can be found that DEM is well developed and useful to investigate the granular behavior after comparing the results with previous work.…”
supporting
confidence: 56%
See 4 more Smart Citations
“…So far, DEM has become one of the most powerful simulation methods for granular behaviors. In the ironmaking field, many researches [5][6][7][8] had been studied about the granular behavior based on DEM, and the simulation results coincided well with the experiments and industrial operation. It can be found that DEM is well developed and useful to investigate the granular behavior after comparing the results with previous work.…”
supporting
confidence: 56%
“…The geometries in the 3D model, include the shaft furnace wall and the screws, are made of steel. According to Fernandez [24] and Kou [5], because the screw may be polished by the particle flow, the static friction coefficient between the screw surface and particle is set as 0.364. The simulation parameters are collected in Table 3 [5,8,17,25,26].…”
Section: Model Simulationmentioning
confidence: 99%
See 3 more Smart Citations